The Neuro Patterns Prior to Error Responses in Long-Lasting Working Memory Task: An Event-Related Potential Study - Xiao, Yi; Wu, Jintao; Li, Jiaxuan; Tang, Weicai; Ma, Feng; Sun, Chenhui; Yang, Yuan; Zhan, Wenhao; Wang, Lizhi; Yan, Huijong; Xu, Fenggang; Chen, Shanguang (Frontiers in Behavioral Neuroscience, 2019)
Few studies exist regarding the mechanism prior to response by which cognitive impairment may induce error in a single long-lasting task. The present study intends to clarify the changes in cognition at the electrophysiological level. Changes in amplitude and latency of N1, P2, N2, and P3 components of event related potentials (ERPs) were analyzed for error and correct trials during normal and fatigue. 29 participants had to perform a 2-back working memory task for 100 minutes. The first 10 minutes and the last 10 minutes of the task were used as the normal state and fatigue state of the participant, respectively. EEG data were obtained from the first 10-minute period and the final 10-minute period. The results revealed smaller P3 and P2 amplitudes and longer P2 and N2 latency in the final 10-mintue which was after a long lasting time task. Moreover, smaller P3 and P2 amplitudes but larger N2 amplitudes were observed in error trials for both states. Our results indicated that 1) Long lasting involvement in a cognitive task had a detrimental effect on attention, memory updating and cognitive control, and 2) impaired attention, impairments in memory updating and cognitive control were related to task errors. Our results imply that several impaired cognitive processes were consistently associated with the error and the altered ERP represent the neural patterns prior to error response in mental fatigue state.